When a Blood Donor Has Sickle Cell Trait: Incidental Findings and Public Health - Lee, Lisa M. (The Hastings Center report, 2014)
There are no national recommendations for routine screening for sickle cell trait, nor is there guidance on whether or how to notify donors that they might be tested or identified as having sickle cell trait. As a result, the organizations that collect blood have implemented variable policies about whether and how to inform prospective donors of the possible screening and discovery of this noncommunicable condition. The question of what they should do is related to the broader question of how to handle incidental and secondary findings. In a recent report, the Presidential Commission for the Study of Bioethical Issues outline a framework for handling such findings in the clinical, research, and direct-to-consumer contexts. While the commission's report did not directly address incidental and secondary findings in the public health context of blood donation, it made several overarching recommendations that apply in all contexts where such findings might arise. This essay outlines the special issues raised by discovering sickle cell trait in blood donation and considers the implications of the commission's framework for that problem.